Bamboo Floated-cultivation Model for Upland Kangkong (Ipomoea reptans Poir.) in Tidal Lowland Area - Siti Masreah Bernas; Alamsyah Pohan; Siti Nurul Aidil Fitri; Edi Kurniawan (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Bernas et al. 2012. Bamboo Floated-cultivation Model for Upland Kangkung (Ipomoea reptans Poir.) in Tidal Lowland Area. JLSO 1(2):177-185. South Sumatra Province has a high potential of swampland for expansion of floating agriculture system. Swampland in Palembang, for instance, can be adapted for floating vegetable cultivation. The experiments on floating agricultural system have been done by using wasted plastic glass, bamboo for rice and glutinous rice with the application of Hycinth and water Fern compost. The purpose of this research was to build bamboo rafts which were suitable for growing kangkong (Ipomoea reptans). Previous rafts which contained water saturated soil for rice growing needed to be adjusted for kankong cultivation which prefer unsaturated soil. Two bamboo rafts were built using four plastic containers in bottom corners.The first raft was filled with soil plus compost (ratio 1:1) and the other was filled only with swamp soil. Kankong seeds were planted with the distance of 25 cm by 25 cm. Data were collected weekly and analysed statistically using t-test. Results showed that when the rafts were supported by two bamboos, plants were died due to excessive water. Plants grew well after the rafts were supported by plastic containers. Composting significantly increased plant height, number of leaves, plants fresh and dried weight. Plant height treated with compost was 38 cm compared to that without compost treatment which was 28 cm. Fresh plant weight was 149 g/bunch with compost treatment and 25 g/bunch without. Thus, low fertility of swamp soil only required compost to increase nutrients content for plant growth.This research concluded that plant can be cultivated cheaply and environmentally safe in swampland. Further experiments such as replacing plastic container in raft construction and growing other vegetables on the raft were proposed.